Estudo perceptivo sobre avaliação do ensino-aprendizagem no curso de pedagogia na modalidade de Educação à distância da universidade Estadual do Ceará – UECE - Saraiva, Rochely Silva de Lima (2015)
This thesis aims to unveil, in the students’ context, the characteristics of the teaching-learning process in the distance modality; the meaning and the appreciation of evaluation practices, in the Education graduate program at the State University of “Ceará”. The research was based on a hermeneutic approach and it was supported by phenomenological interpretation. Heideggers’ conceptions were the foundation to analyze the meaningful units as well as the subjects’ speeches. The phenomenology of Merleau-Ponty was also a theoretical framework for the research, in order to reveal the essence of the phenomenon, that is, the significance and meanings of the subjects’ experiences. The research took place in the years of 2012 and 2013 in the “Maranguape” and “Campos Sales” university campi. The criteria for choosing these centers were the location, what means the proximity or distance from the main University campus, in Fortaleza, the main campus of this university. The subjects were twenty four students which were enrolled in the distance program, four preceptors and the students’ professors. A semi-structured interview was utilized as the instrument to collect the data. The study searched to interpret the thoughts and the experiences of the subjects, as well as their awareness of “being in the world” in a High Education environment. The results related to the students’ speeches reveal that their intentions about the future are directly linked to the process of decision making, in relation to the opportunities. This fact was evidenced by the desire to restore self-esteem and by the decision to enroll in a graduate program, which means that the Dasein stems from the student themselves and from the ways they relate themselves with the world. In this distance education modality, the students were aware that “being in the world” is related to the way they utilize the object (technics/EaD), preferable, as an optional instrument which is important to conclude the graduate program and to overcome the limitations related to its utilization. Thus, they transform the distance reality concerning EaD computer, by means of active exploration and optimistic expectative, while they are enrolled in the program. The study also showed that the knowledge construction depends on stimulating factors which are present in an atmosphere favorable to learning such as interaction, empathy among persons and the educational program structure which foster dialogues, conexions and multiple learning. The feeling of “being in the world” is built by the evaluation procedures of the distance program that should be based on a constructivist approach, in which the processus makes possible the drive to act, to anticipate and to advance. It was observed in the program the practice of first generation evaluation procedures; however, the speeches of the professors reveal they believe in a constructive evaluation. So, it is suggested the adoption of a Dialogic Evaluative Act, since it articulates, in the evaluation process, a dialogue among philosophical, pedagogic, political and curricular principles of formation. Therefore, in the evaluative procedures, the Dasein is the center of this process and should be integral, dialogic and historical. In this way, it may foster the development of independent and responsible experiences which allow an active, conscious and meaningful learning. In this context, it is possible to affirm that the essence of the evaluation procedures consists in the constructive possibilities that it develops in the students such as autonomy and self formation.